Electron Microscopy Views of Dimorphic Chloroplasts in C4 Plants - Mai, Keith Ka Ki; Gao, Peng; Kang, Byung-Ho (Frontiers in Plant Science, 2020)
C4 plants enhance photosynthesis efficiency by concentrating CO2 to the site of Rubisco action. Chloroplasts in C4 plants exhibit structural dimorphism because thylakoid architectures vary depending on energy requirements. Advances in electron microscopy imaging capacity and sample preparation technologies allowed characterization of thylakoid structures and their macromolecular arrangements with unprecedented precision mostly in C3 plants. The thylakoid is assembled during chloroplast biogenesis through collaboration between the plastid and nuclear genomes. Recently, the membrane dynamics involved in the assembly process has been investigated with 3D electron microscopy, and molecular factors required for thylakoid construction have been characterized. The two classes of chloroplasts in C4 plants arise from common precursors, but little is known about how a single type of chloroplasts grow, divide, and differentiate to mature into distinct chloroplasts. Here, we outline the thylakoid structure and its assembly processes in C3 plants to discuss ultrastructural analyses of dimorphic chloroplast biogenesis in C4 plant species. Future directions for electron microscopy research of C4 photosynthetic systems are also proposed.